Jeremiah [videorecording (DVD)] - Winer, Harry Stuart; Dempsey, Patrick, 1966-; Reed, Oliver, 1938-1999; Brandauer, Klaus Maria (Bible collection., 2023)
Jeremiah tells the story of a prophet who abandoned his family to relay God's message to Jerusalem and, once his prophecy was fulfilled, experienced Jerusalem's destruction.